Prenatal Exposure to Bisphenol A Disrupts Mouse Fetal Liver Maturation in a Sex‐Specific Manner. Issue 2 (1st September 2015) - DeBenedictis, Bianca; Guan, Haiyan; Yang, Kaiping
ABSTRACT: Bisphenol A (BPA) is one of the most prevalent endocrine disrupting chemicals in the environment. Developmental exposure to BPA is known to be associated with liver dysfunction and diseases, such as hepatic steatosis, liver tumors, metabolic syndrome, and altered hepatic gene expression, and DNA methylation profiles. However, the effects of BPA on rodent liver development are unknown. The present study was undertaken to address this important question using the mouse as an experimental model. Pregnant mice were exposed to BPA via diet from embryonic day 7.5 (E7.5) to E18.5. At E18.5, fetal livers were collected, and analyzed for changes in the expression of key hepatocyte maturation markers. We found the following significant alterations in BPA‐exposed female but not male fetal livers: (a) levels of the mature hepatocyte markers, albumin and glycogen synthase proteins, were decreased (−65% and −40%, respectively); (b) levels of the immature hepatocyte marker, α‐fetoprotein, were increased (+43%); (c) the level of C/EBP‐α protein, the master transcription factor essential for hepatocyte maturation, was down‐regulated (−50%); and (d) the level of PCNA protein (marker of proliferation) was elevated (+40%), while that of caspase‐3 protein and activity (markers of apoptosis) was reduced (−40% and −55%, respectively), suggestive of a perturbed balance between cell proliferation and apoptosis in BPA‐exposed female fetuses. Taken together, these findings demonstrate that prenatal exposure to BPA disrupts the mouse fetal liver maturation in a sex‐specific manner, and suggest a fetal origin for BPA‐induced hepatic dysfunction and diseases. J. Cell. Biochem. 117: 344–350, 2016. © 2015 Wiley Periodicals, Inc.